The Oral Microbiome and Cancer - Irfan, Muhammad; Delgado, Renata Zoraida Rizental; Frias-Lopez, Jorge (Frontiers in Immunology, 2020)
There is mounting evidence that members of the human microbiome are highly associated with a wide variety of cancer types. Among oral cancers, oral squamous cell carcinoma (OSCC) is the most prevalent and most commonly studied, and it is the most common malignancy of the head and neck worldwide. However, there is a void regarding the role that the oral microbiome may play in OSCC. Previous studies have not consistently found a characteristic oral microbiome composition associated with OSCC. Although a direct causality has not been proven, individual members of the oral microbiome are capable of promoting various tumorigenic functions related to cancer development. Two prominent oral pathogens, Porphyromonas gingivalis, and Fusobacterium nucleatum can promote tumor progression in mice. P. gingivalis infection has been associated with oro-digestive cancer, increased oral cancer invasion, and proliferation of oral cancer stem cells. The microbiome can influence the evolution of the disease by directly interacting with the human body and significantly altering the response and toxicity to various forms of cancer therapy. Recent studies have shown an association of certain phylogenetic groups with the immunotherapy treatment outcomes of certain tumors. On the other side of the coin, recently it has been a resurgence in interest on the potential use of bacteria to cure cancer. These kinds of treatments were used in the late nineteenth and early twentieth centuries as the first line of defense against cancer in some hospitals but later displaced by other types of treatments such as radiotherapy. Currently, organisms such as Salmonella typhimurium and Clostridium spp. have been used for targeted strategies as potential vectors to treat cancer. In this review, we briefly summarize our current knowledge of the role of the oral microbiome, focusing on its bacterial fraction, in cancer in general and in OSCC more precisely, and a brief description of the potential use of bacteria to target tumors.